2016
DOI: 10.1542/peds.2015-1633
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Concussion in Youth Ice Hockey Players

Abstract: Ice hockey is a fast-paced collision sport that entails both intentional (ie, body checking) and incidental contact that may involve the head. The objective of this study was to determine the incidence of concussions in relation to games/practices and age among competition-level youth ice hockey players (ages 12-18 years).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…Game role -forward and fullback. In the distribution of groups were taken into account the features of physical development: the beginning of the pubertal period is characterized by great variability in the parameters of physical development [19]. The distribution for groups was conducted in steps of one year: 13 years old hockey players (mean age 13.31 ± 0.48 years, n = 16); 14 years old hockey players (age 14.22 ± 0.42 years, n = 26); 15 years old hockey players (age 15.22 ± 0.43 years, n = 18); 16 years old hockey players (age 16.24 ± 0.44 years, n = 23).…”
Section: Pedagogics Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…Game role -forward and fullback. In the distribution of groups were taken into account the features of physical development: the beginning of the pubertal period is characterized by great variability in the parameters of physical development [19]. The distribution for groups was conducted in steps of one year: 13 years old hockey players (mean age 13.31 ± 0.48 years, n = 16); 14 years old hockey players (age 14.22 ± 0.42 years, n = 26); 15 years old hockey players (age 15.22 ± 0.43 years, n = 18); 16 years old hockey players (age 16.24 ± 0.44 years, n = 23).…”
Section: Pedagogics Psychologymentioning
confidence: 99%
“…In various countries, power collisions have been permitted since the age of 10-12 years. This leads to a significant increase in the risk of injury to hockey players of childhood and adolescence [19][20][21]. Hockey agents and scouts of hockey teams pay much attention to the analysis of the indicators of game statistics and physical development parameters of prospective players [22].…”
mentioning
confidence: 99%
“…Kontos et al (2016) found that 40% of incurred concussions in youth ice hockey were due to illegal contact. More importantly, studies have suggested that limiting contact in various sports may reduce the number of concussive injuries.…”
Section: Recommendationsmentioning
confidence: 99%
“…Mild traumatic brain injuries (mTBI), have become an inevitable outcome of many contact sports such as ice hockey which has one of highest incidence rates of brain trauma [1][2][3][4]. About 1.8 to 3.6 million cases of mTBI have been reported for sport and recreational activities with 65% of them occurring among youth athletes (5 to 18 years old) [5,6]. Prevalence of concussive injuries and the lifetime neurodegenerative disorders associated with them have risen many concerns in the past decades which has been the motivation of much research [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%